Redesigning Automotive Tool: Usability of an Improvised Combination Wrench for Practical Education - Capuno, Jhon Froy; Gahob, Ritchie; Lequigan, Mailyn; Lequigan, Reo; Cañon, Anaclito; Dela Calzada, Jeffrey (The Indonesian Institute of Science and Technology Research, 2025)
The automotive industry's rapid technological shift presents a challenge for vocational education, as traditional tools may not align with modern needs. Thus, this study evaluates the acceptability of an Improvised Combination Wrench (ICW) as a cost-effective instructional tool for automotive technology. Using a mixed-methods approach with 60 participants (students, instructors, and experts) the research assessed the tool's design, functionality, and safety. The findings indicate the ICW is highly acceptable and usable, with high ratings for its functionality (grand mean: 4.60), aesthetics (4.63), and users' safety (4.63). It is consistently perceived the tool as a natural extension of the hand, appreciating its effectiveness, durability, and ergonomic design. However, a significant difference in perception was found among the three user groups (F=166.1522, p<.001), highlighting varied views based on experience. The main challenges identified were a lack of sufficient torque, non-standard sizing, and tool slippage. In conclusion, the ICW is a viable and effective teaching tool despite these limitations. It is recommended that the university formally adopt a standardized, redesigned version of the wrench, with enhancements to address the identified challenges, and implement a comprehensive training module to ensure its proper and safe use in the curriculum.